A comprehensive sintering mechanism for TBCs‐Part II: Multiscale multipoint interconnection‐enhanced initial kinetics. Issue 9 (18th May 2017) - Li, Guangrong; Xie, Hua; Yang, Guanjun; Liu, Gang; Li, Chengxin; Li, Changjiu
Abstract: During thermal exposure, the sintering process of the plasma‐sprayed thermal barrier coatings (PS‐TBCs) presents significant two‐stage kinetics, as reported in the Part I. As a companion study, this part aims to reveal the mechanism responsible for the ultrafast sintering kinetics when initially exposed, since the initial short stage (stage‐I) often finishes most increment of the mechanical and thermal properties. A detailed examination of the pore healing behavior was carried out, based on the experimental result in Part I that the dominant structural change at the stage‐I is the significant healing at intersplat pore tips. Results show that the smooth splat surface, which made up the wedge‐shaped intersplat pores, changed to a rough surface with multiscale convexs after high‐temperature thermal exposure. Moreover, the multiscale roughening is highly sensitive to various orientations of the columnar grains inside the splats. Subsequently, multipoint connection between the counter‐surfaces of the intersplat pores was formed by the bridging of multiscale convexs. This multiscale multipoint connection between pore surfaces significantly accelerated the healing of intersplat pores, which can be dominantly responsible for the ultrafast sintering kinetics at the stage‐I. This comprehensive sintering mechanism could offer some positive suggestions toward prolonging the thermal‐insulating effect of TBCs.